Distribution and inhibition of Thiobacillus ferrooxidans in relation to acid drainage from coal waste dumps - Mare, Johan,1959- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.